TECHNOLOGIES OF NON-FORMAL EDUCATION:EUROPEAN AND DOMESTIC EXPERIENCE - KOVALCHUK, S.; MARTYNOVA, L.; TANASIICHUK, А. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Until recently, the main criterion that companies paid attention to when looking for employees was the presence of a diploma, which indicated a narrow professional specialization. Everything else was considered a positive but not a necessary addition. In recent years, the emphasis on the importance of flexible skills has grown worldwide. It is no longer enough to have knowledge and professional skills, but it is important how this knowledge will turn into a result. Behavior of employees in the team, attitude to work, communication skills with partners, team leadership skills, ability to cope with problems and stressful situations, the ability to think critically and participate in socio-political processes, the ability to live in diversity and dynamic change in society, skills learning, public speaking and communication skills, office programs, presentations, team experience, approaching people and resolving conflict situations, work ethic, language training, communication skills, emotional intelligence and a number of other personal qualities play an important role in the workplace. place and while looking for work in the modern labor market. In this regard, an important component of the modern educational space has become non-formal education (nonformaleducation), which provides holistic development of the individual, increasing its professional and social adaptation in society, the development of its abilities and capabilities.The article emphasizes the need to develop flexible skills of graduates of higher education institutions through the system of non-formal education. This directs educational service providers to address gaps in the development of flexible skills, taking into account the goals of sustainable development on a global scale. The preconditions for the emergence of the modern educational category "continuing education" are considered. The differences between non-formal and formal education are determined, the signs of non-formal education are determined. An analysis of key competencies that are formed in the process of non-formal learning. Approaches to the formation of universal skills are generalized and the classification of universal competencies (soft skills) is developed, which change adequately to the requirements of the time. It is proved that in order to increase the competitiveness of participants in the educational space for employment, it is necessary to establish the interaction of formal, non-formal and informal education.
Keywords: formal education; non-formal education; hard skills; soft skills; functional literacy; classification of universal competencies